Molecular Research of Endometrial Pathophysiology - Viganò, Paola (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The endometrium has been the subject of intense research in a variety of clinical settings, because of its importance in the reproductive process and its role in women's health. In the past 15 years, significant efforts have been invested in defining the molecular phenotype of the receptive phase endometrium as well as of various endometrial pathologies. Although this has generated a wealth of information on the molecular landscape of human endometrium, there is a need to complement this information in light of the novel methodologies and innovative technical approaches. The focus of this International Journal of Molecular Sciences Special Issue is on molecular and cellular mechanisms of endometrium and endometrium-related disorders. The progress made in the molecular actions of steroids, in the metabolism of steroids and intracrinology, in endometrial intracellular pathways, in stem cells biology, as well as in the molecular alterations underlying endometrium-related pathologies has been the focus of the reviews and papers included.